2021
DOI: 10.1088/1755-1315/802/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Waste bank system improvement for electronic waste recycling in Indonesia: a case study of Padang City

Abstract: Currently, Indonesia does not practice a formal management system for electronic waste (e-waste). The informal sector mostly conducts e-waste handling with limited concern for the environment and human health. The most challenging issue is establishing a collection system across the nation that is widely accepted by communities. Even though waste bank (WB) system does not practice e-waste collection, it may offer a solution since the system has been emerged as an accepted recycling program by Indonesian citize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Indonesia has established Law Number 18 of 2008 on Waste Management which shifts the paradigm from waste disposal to waste recycling (Raharjo, Wulandari and Fitriani, 2021) The Recycling Potential of Solid Waste in Jatinegara Sub-district, East Jakarta Kuntaryo, Purwaningrum, Tazkiaturrizki, Minarti, Ashardiono p-ISSN 2579-9150;e-ISSN 2579-9207 102 management system by observing the potential of waste that can be recycled (Owojori et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia has established Law Number 18 of 2008 on Waste Management which shifts the paradigm from waste disposal to waste recycling (Raharjo, Wulandari and Fitriani, 2021) The Recycling Potential of Solid Waste in Jatinegara Sub-district, East Jakarta Kuntaryo, Purwaningrum, Tazkiaturrizki, Minarti, Ashardiono p-ISSN 2579-9150;e-ISSN 2579-9207 102 management system by observing the potential of waste that can be recycled (Owojori et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been undertaken on numerous topics, such as economics and finance [13], social and legal [14,15], institutional [16], environment [17], and technology [18]. The latest publications on waste bank management in Indonesia have been carried out by some scholars [19][20][21]. This paper aimed to provide substantive insights into the sustainability aspect of waste banks.…”
Section: Introductionmentioning
confidence: 99%
“…13/2012 as recycling advice. WB grows ten times in five years, distributing to 206 districts/cities throughout 30 provinces (Raharjo et al, 2021). Additionally, prior research indicated that WB must be established at the source and municipal levels.…”
Section: Introductionmentioning
confidence: 99%
“…WB also serves as a drop-off location for an extended producer responsibility (EPR) program and a collection location for managing e-waste. Six of Indonesia's top WBs are currently operational: Surabaya Bina Mandiri WB, Malang WB, East Jakarta, Mekarsari RW 03 WB, Makassar Tallo WB, Bantul Gemah Ripah WB, and Banjarmasin Central WB (Raharjo et al, 2021). WB typically accepts commercial waste such as paper, newspaper, cardboard, several kinds of plastic bottles, and different kinds of metals.…”
Section: Introductionmentioning
confidence: 99%